Membangun Karakter Peserta Didik MI/SD Melalui Media Komik Pembelajaran - Laksana, Sigit Dwi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Problems of students’ character are currently the main focus in the education realm. The role of the family, teachers, and the society is critical in shaping the character of children.The weakness of character-based learning in an educational institution has been the key factor on the problem of student characters. The teacher in the learning process is often lessinovative and creative in designing the learning process, especially in terms of learning media design. Comic is one of media that can help students and can replace the position of teachers in learning activities both inside and outside the classroom. Comic can be used in a two-way learning process, namely as a teaching tool and as a medium for shaping the character of the students. Based on observation field, it is known that in the process of learning, comic as instructional medium has never been utilized. Therefore, the presence of learning media in the form of comics is expected to assist the teacher in the learning process and helps in forming the character of students. Comic languages using polite language are expected to avoid impolite languages and not in accordance with the objectives of education character. This also inspires the use of instructional media comic contents of learning materials in elementary school. Comics as a medium of learning is able to build the foundations of character for learners and are ultimately capable of constructing human characters that are intact and resilient.